Tissue Competence Imprinting and Tissue Residency of CD8 T Cells - Krzysiek, Roman; de Goer de Herve, Marie -Ghislaine; Taoufik, Yassine (Frontiers in Immunology, 2013)
T cell immunity is characterized by striking tissue specialization. Tissue-specificity imprinting starts during priming by tissue-derived migratory dendritic cells in the non-random, specialized micro-anatomical area of the draining lymph node and is influenced by constitutive and induced cues from local environment. Besides tissue-specific effectors, memory cells also exhibit a tissue-specificity. Long-lived tissue-resident memory T cells likely play a considerable role in preventing pathogen invasion. Understanding of the mechanisms of tissue-specialization of T cells is of major importance for the design of optimal vaccination strategies and therapeutic interventions in tissue/organ-specific inflammatory diseases. The present review summarizes our current knowledge and hypothesis about tissue-specificity imprinting and tissue residency of T cells.